Current Clinical Oncology
DOI: 10.1007/978-1-59745-215-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology of Colon Cancer

Abstract: SummaryColorectal cancer affects approx 140,000 people in the United States each year, resulting in more than 55,000 deaths. Colorectal cancer develops as the result of the progressive accumulation of genetic and epigenetic alterations that lead to the transformation of normal colonic epithelium to colon adenocarcinoma. The loss of genomic stability is a key molecular and pathophysiological step in this process and serves to create a permissive environment for the occurrence of alterations in tumor suppressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 159 publications
(193 reference statements)
0
1
0
Order By: Relevance
“…In particular, mutations of APC , KRAS , SMAD4 , DCC , TP53 and DNA mismatch repair genes are the most common and characteristic molecular events. [ 21 23 ] Due to the popularity of single cell sequencing and the study of gene and genomics, more and more new tumor markers have been applied, especially in colorectal cancer. Yang et al found seven differentially expressed mRNAs which were associated with prognosis in colon cancer patients by transcriptomic analysis, involving (SGCG, CLDN23, SLC4A4, CCDC78, SLC17A7, OTOP3, and SMPDL3A).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, mutations of APC , KRAS , SMAD4 , DCC , TP53 and DNA mismatch repair genes are the most common and characteristic molecular events. [ 21 23 ] Due to the popularity of single cell sequencing and the study of gene and genomics, more and more new tumor markers have been applied, especially in colorectal cancer. Yang et al found seven differentially expressed mRNAs which were associated with prognosis in colon cancer patients by transcriptomic analysis, involving (SGCG, CLDN23, SLC4A4, CCDC78, SLC17A7, OTOP3, and SMPDL3A).…”
Section: Discussionmentioning
confidence: 99%